2020
DOI: 10.1002/ehf2.12984
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement with anti‐mitochondrial antibody‐positive myositis mimicking cardiac sarcoidosis

Abstract: Anti-mitochondrial antibody (AMA)-positive myositis is an atypical inflammatory myopathy characterized by chronic progressive respiratory muscle weakness, muscular atrophy, and cardiac involvement. Arrhythmias, cardiomyopathy, and myocarditis have been reported as cardiac manifestations. Herein, we present the first report of a patient diagnosed with having AMA-positive myositis with cardiac involvement mimicking cardiac sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However, the response of cardiac involvement to immunosuppressive treatment is unknown, and the cardiac outcomes in case reports are contradictory. Interestingly, some cases showed that cardiac involvement worsened or remained unchanged, even after glucocorticoid therapy improved muscle weakness and CK levels 25–28 . This outcome could be explained by the finding that cMRI detected myocarditis manifestations after glucocorticoid treatment in inflammatory myositis, which is clinically considered to be in remission 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the response of cardiac involvement to immunosuppressive treatment is unknown, and the cardiac outcomes in case reports are contradictory. Interestingly, some cases showed that cardiac involvement worsened or remained unchanged, even after glucocorticoid therapy improved muscle weakness and CK levels 25–28 . This outcome could be explained by the finding that cMRI detected myocarditis manifestations after glucocorticoid treatment in inflammatory myositis, which is clinically considered to be in remission 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some cases showed that cardiac involvement worsened or remained unchanged, even after glucocorticoid therapy improved muscle weakness and CK levels. [25][26][27][28] This outcome could be explained by the finding that cMRI detected myocarditis manifestations after glucocorticoid treatment in inflammatory myositis, which is clinically considered to be in remission. 2 Although glucocorticoid therapy might not be sufficient to suppress cardiac inflammation, there is no clear evidence for the use of additional immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…In a large North American study on inflammatory myopathy, albeit AMA prevalence was extremely low (0.006%), it was associated with a distinct phenotype with severe cardiac involvement, as severe conduction abnormalities and arrhythmias, cardiomyopathy, ventricular dilatations, and myocarditis, oftentimes occurring all in the same patient [97]. Other authors suggested that AMA-associated myopathy mimics sarcoidosis heart involvement, based on magnetic resonance findings, showing left ventricle systolic dysfunction [98]. Of interest, in the case of cardiomyopathy and myocarditis, treatment with immunosuppression could improve cardiac function.…”
Section: Inflammatory Myositismentioning
confidence: 99%
“…These patients exhibit various characteristics, including cardiac involvement, more protracted course, and occasional association with primary biliary cirrhosis, as expected in overlap myositis (OM) [6][7][8][9] The most common cardiac manifestations seen in these patients are myocarditis, atrial and ventricular arrhythmias and cardiomyopathy, while common hepatic manifestations include primary biliary cirrhosis and autoimmune hepatitis. 10,11 Early identification of underlying cardiac dysfunction may carry implications toward patient management, including closer monitoring and the use of higher doses of glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AMA testing owing to its wide availability and reasonable cost may help to identify and correct previously misdiagnosed cases following up with gastroenterology and cardiology, alongside difficult to treat autoantibody negative IIM which are confused with muscle dystrophies but may respond to immunosuppressants. 5,[11][12][13] Further, Indian patients with IIM are known to exhibit distinct clinicalphenotypic features. [14][15][16][17] Current literature on AMA-positive IIM is limited to short case series, and amounts to a heterogeneous group, with varied clinical features.…”
Section: Introductionmentioning
confidence: 99%